The Influence of Job Satisfaction and Quality of Work Life on Employee Performance: The Mediating Role of Organizational Commitment - Muhammad Zain Alfain; Noekent, Vitradesie; Rama Fajar Shidiq (Universitas Negeri Semarang, 2024)
This study examines the influence of job satisfaction (JS) and quality of work life (QWL) on employee performance (EP), with organizational commitment (JS) as a mediating variable at PT Asia Pacific Fibers Kendal. Through a quantitative approach, data were obtained from 211 employees of PT Asia Pacific Fibers Kendal. The test results indicate that JS has a non-significant positive influence on EP, while the QWL and OC have a significant positive influence. The findings suggest that OC mediates JS and QWL towards EP. This research provides an understanding of the factors and conditions of EP, JS, QWL, and OC at PT Asia Pacific Fibers Kendal and other stakeholders to enhance competitiveness and sustainability in the manufacturing industry. Future research is expected to be able to use supervisor/peer-rated questionnaire methods and generalize the ratio between males and females to strengthen previous research; it is expected to generalize the research findings